Democracy and Popular Rebellion in Contemporary Brazil. Issue 4 (December 2016) - Martins, Mônica Dias
In contrast to the media portrayal of Brazil as a country on the brink of the abyss, this article shows the resistance opportunities of the social movements organized to defend their rights and to reaffirm their commitment to democracy. The bourgeoisie allied with the congressional conservative faction has attempted to attack the few working-class gains made in recent years through a constitutional coup d'état against the president whose mandate was legitimized at the polls. We, Brazilians, are living through an ideological struggle rich in possibilities for increasing popular political participation, the distribution of wealth, and national sovereignty. Brazil is the key to a South American integration that differs from the interests of the great powers and their corporations. At play is the future of the continent's people.